Preparation method and application of anti-bending perovskite thin film

By introducing PDPP as an anti-solvent additive in perovskite solar cell films, the problem of the film being easily damaged when bending is solved, its bending resistance is significantly improved, and excellent in efficient and stable perovskite solar cells are achieved. Photoelectric conversion efficiency.

CN119403417APending Publication Date: 2025-02-07MINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417124.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing perovskite solar cell films are prone to damage when bending and lack effective bending resistance.

Method used

Poly(diphenoxyphosphazene) (PDPP) was used as an additive and introduced into green antisolvent ethyl acetate. The MAPbI3 perovskite precursor solution was spin-coated on the electron transport layer by spin coating, and the thermal annealing process was carried out. Modified anti-solvent is added to improve the anti-bending properties of the film.

Benefits of technology

The high bending resistance of perovskite solar cell film was achieved. After the device was bent 1,000 times at room temperature, the photoelectric conversion efficiency remained 78%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403417A_ABST
    Figure CN119403417A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bending-resistant perovskite thin film, and the method comprises the steps: carrying out the spin coating of an MAPbI3 perovskite precursor solution on an electron transmission layer, adding a modified anti-solvent, and carrying out the thermal annealing treatment, thereby obtaining the bending-resistant perovskite thin film. Wherein the MAPbI3 perovskite precursor solution comprises a solute and a solvent, the solvent is a mixed solvent of N, N-dimethylformamide and dimethyl sulfoxide, and the solute is lead iodide and methyl amine iodine; the modified anti-solvent is ethyl acetate containing PDPP. According to the optimized perovskite solar cell, the PCE (Peroxide Electrophoresis) is up to 21.36%, the hysteresis effect which can be almost ignored is realized, and meanwhile, the excellent bending resistance is also shown. According to the simple, green and low-cost method for preparing the perovskite thin film and the solar cell thereof in the air environment, the PCE and the stability of the device are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a preparation method of a bending-resistant perovskite film and application thereof. Background Art

[0002] With the increasingly rapid development of modern society, traditional non-renewable fossil energy can no longer meet people's rapidly growing energy needs, and the trend of it being gradually replaced by renewable clean energy has emerged. Photovoltaic power generation is a sustainable, pollution-free green energy development technology that can directly convert solar radiation energy into electrical energy. In recent years, as an emerging photovoltaic technology, organic-inorganic hybrid perovskite solar cells (PSCs) with the advantages of low cost and high efficiency have attracted widespread attention. As early as 2009, scientific researchers began to study PSCs. After more than ten years of development, its highest power conversion efficiency (PCE) world certified record has been rapidly improved from the initial 3.8% to 26.7%.

[0003] Antisolvent engineering is one of the many ways to introduce additives into the perovskite light absorbing layer. Because the preparation process of perovskite films often uses antisolvents such as ethyl acetate (EA) and chlorobenzene (CB) that are miscible with the deposition solvent in the precursor solution but insoluble in the perovskite salt to adjust its surface morphology and crystallization process, researchers are increasingly interested in the development of antisolvent engineering. The rich functional groups of polymers can assist the crystallization of perovskite grains. When added to the antisolvent, they can intervene in the crystallization process of perovskite at the best time to maximize their own auxiliary ability. At the same time, the long chains of flexible polymers aggregated between the grain boundaries can significantly improve the overall flexibility / bending resistance of the film. In addition, the green preparation process of PSCs in an air environment without the use of a glove box can reduce energy consumption and protect researchers from more toxic chemicals. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a bending-resistant perovskite film.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a bending-resistant perovskite film, characterized in that: the bending-resistant perovskite film is a MAPbI 3 The perovskite precursor solution is spin-coated on the electron transport layer and a modified anti-solvent is added, and then thermally annealed to obtain;

[0008] Wherein, the MAPbI 3 The perovskite precursor solution comprises a solute and a solvent, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, the solute is lead iodide and methylamino iodide, and the modified anti-solvent is ethyl acetate containing PDPP.

[0009] As a preferred embodiment of the preparation method of the present invention, the concentration of the PDPP is 0.01-5.0 mg / ml.

[0010] As a preferred embodiment of the preparation method of the present invention, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide in the solvent is 6 to 9:1, and the molar ratio of lead iodide to methylamino iodide in the solute is 1:1.

[0011] As a preferred embodiment of the preparation method of the present invention, wherein: the MAPbI 3 The preparation method of the perovskite precursor solution comprises: mixing a solute with a solvent, heating the mixture at 55° C. to 65° C., and stirring the mixture at a rotation speed of 200 to 500 rpm for 0.5 to 2 hours.

[0012] As a preferred embodiment of the preparation method of the present invention, the spin coating time lasts for 40 seconds, and the process is divided into two sections; the first section is 10 seconds, and the rotation speed increases from static to 2000 rpm and maintains at an acceleration of 500 rpm / s; the second section is to continue spinning for 30 seconds without pausing, and the rotation speed increases from 2000 rpm to 3500 rpm at an acceleration of 1000 rpm / s.

[0013] As a preferred embodiment of the preparation method of the present invention, the annealing temperature is 90° C. to 110° C., and the annealing time is 10 to 40 minutes.

[0014] As a preferred embodiment of the preparation method of the present invention, wherein: the modified anti-solvent and MAPbI 3 The volume ratio of the perovskite precursor solution is 100-500:70.

[0015] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a bending-resistant perovskite film to obtain a bending-resistant perovskite film.

[0016] As a preferred solution of the bending-resistant perovskite film of the present invention, the thickness of the bending-resistant perovskite film is 300-500 nm.

[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a bending-resistant perovskite film in a perovskite solar cell, characterized in that: the preparation method of the perovskite solar cell comprises sequentially preparing an anode, an electron transport layer, a photoactive layer, a hole transport layer and a cathode; wherein the photoactive layer is between the anode and the cathode, the electron transport layer is between the anode and the photoactive layer; the hole transport layer is between the cathode and the photoactive layer; the anode is ITO, the electron transport layer is SnO 2 , the photoactive layer is MAPbI 3 , the hole transport layer is Spiro-OMeTAD, and the cathode is Ag.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention adopts a new polymer double passivation technology, by introducing poly (diphenyloxyphosphazene) (PDPP) as an additive into the green anti-solvent ethyl acetate, and precisely modifying it at the critical moment of perovskite grain crystallization. The polymer long chain of PDPP is composed of nitrogen and phosphorus elements alternately, and a large number of oxygen groups and benzene rings are inserted on both sides at the same time. Through Lewis acid-base interaction, the phosphorus oxygen functional group can form a strong chemical bond with lead (Pb), while the nitrogen element can form a hydrogen bond with methylamine (MA). The formation of these two chemical bonds can simultaneously fill the vacancies caused by I and Pb. At the same time, the benzene ring has certain electrochemical activity and hydrophobicity, which is beneficial to improve the efficiency and stability of the device. On the other hand, the flexible polymer long chain of PDPP can easily aggregate on the perovskite grain boundary to improve the overall bending resistance of the film.

[0020] (2) MAPbI prepared by the present invention after PDPP optimization 3 The perovskite solar cells based on PDPP modified perovskite layer achieved a photoelectric conversion efficiency of up to 21.36% and almost negligible hysteresis effect. The flexible polyethylene naphthalate (PEN) substrate device based on PDPP modified perovskite layer showed excellent anti-bending performance. After the unpackaged device was bent at a radius of 6 mm for 1000 cycles at room temperature, the normalized PCE still maintained 78% of the initial value. Therefore, when PDPP is used as an anti-solvent modifier for perovskite films, efficient and stable perovskite solar cells can be prepared in an air environment without a glove box. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0022] Figure 1 It is a current density-voltage test curve diagram of the perovskite solar cells of Examples 1-3 of the present invention and Comparative Example 1.

[0023] Figure 2 MAPbI of Examples 1-3 of the present invention and Comparative Example 1 3 UV-Vis image of perovskite film.

[0024] Figure 3 MAPbI of Example 1 of the present invention and Comparative Example 1 3 SEM image of perovskite film.

[0025] Figure 4 MAPbI of Example 1 of the present invention and Comparative Example 1 3 PL spectrum of perovskite film.

[0026] Figure 5 MAPbI of Example 1 of the present invention and Comparative Example 1 3 Optical images and surface SEM images of perovskite films.

[0027] Figure 6 Graph showing the normalized power conversion efficiency (1000 bending cycles recorded at room temperature) of Example 1 of the present invention and Comparative Example 1.

[0028] Figure 7 This is a current density-voltage test curve diagram of the perovskite solar cells of Comparative Examples 2-4.

[0029] Figure 8 Schematic diagram of the chemical bond formation between PDPP polymer chains and the perovskite lattice. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.

[0034] Table 1

[0035]

[0036]

[0037]

[0038] Example 1

[0039] The device structure of a bending-resistant perovskite thin-film solar cell provided by the present invention is:

[0040] ITO / SnO 2 / MAPbI 3 / Spiro-OMeTAD / Ag.

[0041] The anode is indium tin oxide (ITO), the hole transport layer is 2,2′,7,7′-tetrakis(N,N-dimethoxy-aniline)-9,9′-spirobifluorene (Spiro-OMeTAD), and the photoactive layer is methylamino lead iodide (MAPbI 3 ), the electron transport layer is tin dioxide (SnO 2 ), the cathode is silver (Ag).

[0042] The present invention provides a method for preparing a bending-resistant perovskite film and a solar cell thereof:

[0043] (1) The original concentration of SnO was 15 wt.% 2 The hydrocolloid dispersion was diluted with deionized water to 3 wt.% and used as a precursor solution for the electron transport layer. The SnO 2 Precursor solution.

[0044] (2) 1M PbI 2 The MAI solid powder was dissolved in a mixed solvent of 0.6 ml N, N-dimethylformamide and 78 μl dimethyl sulfoxide as a perovskite precursor solution; it was then heated at 65 °C and stirred at 280 rpm for 1.5 h before use.

[0045] (3) 1.5 mg of PDPP was dissolved in 1 ml of ethyl acetate (EA) as the modified green antisolvent with a concentration of 1.5 mg / ml.

[0046] (4) FK209 and LiTFSI powders were dissolved in acetonitrile solvent at concentrations of 170 mg / ml and 150 mg / ml, respectively, and stirred at 300 rpm at room temperature for 1 hour to obtain FK 209 solution and LiTFSI solution as additives for Spiro-OMeTAD solution.

[0047] (5) 65 mg of Spiro-OMeTAD powder was dissolved in 1 ml of chlorobenzene solvent, and 20 μl of tBP solution, 50 μl of FK209 solution and 70 μl of LiTFSI solution (prepared in step 4) were added as additives. The mixture was then stirred at 300 rpm for 1 hour at room temperature to obtain a Spiro-OMeTAD solution.

[0048] (6) The ITO etched glass was ultrasonically treated with acetone, ethanol and isopropanol for 15 minutes respectively. After being fully dried on a heating table at 100°C, the substrate was treated with ultraviolet (UV) ozone for 15 minutes to completely eliminate the excess organic matter remaining on the surface.

[0049] (7) SnO as the electron transport layer (ETL) 2 The solution was spin-coated on a clean ITO-etched glass substrate at 3500 rpm for 25 seconds. After thermal annealing at 150°C for 35 minutes, the substrate was placed in an ultraviolet ozone environment for 10 minutes to obtain a dense electron transport layer.

[0050] (8) The heated and stirred perovskite precursor solution in step (2) was spin-coated on the dense SnO 2 The ethyl acetate modified with PDPP prepared in step (3) is used as a green anti-solvent and added to the perovskite layer 10 seconds before the end of the spin coating process to assist the crystallization of its grains. After a 30-minute thermal annealing treatment at 100°C to help the growth of perovskite crystals, a bending-resistant target perovskite film described in this patent is obtained.

[0051] (9) To prepare a complete perovskite solar cell, a Spiro-OMeTAD solution as a hole transport layer was spin-coated on the perovskite layer at 4000 rpm for 30 seconds. In order to fully oxidize the Spiro-OMeTAD film after deposition, the substrate was placed in a desiccator overnight before evaporating the counter electrode.

[0052] (10) A layer with a thickness of about 80 nm and an active area of ​​0.06 cm was deposited on the top of the device by vacuum thermal evaporation. 2 Silver (Ag) is used as the top electrode. The complete structure is: ITO / SnO 2 / MAPbI 3 Rigid (or flexible) perovskite solar cells based on / Spiro-OMeTAD / Ag.

[0053] The method for preparing a bending-resistant perovskite film and a solar cell thereof described in the present invention, except for the last step of vacuum evaporation of silver electrodes, all other steps are carried out in an air environment, and the specific conditions are room temperature and a relative humidity of about 50%.

[0054] Example 2

[0055] The difference from Example 1 is that in step (3), PDPP is used as a modifier of the ethyl acetate anti-solvent at a concentration of 1.0 mg / ml.

[0056] Example 3

[0057] The difference from Example 1 is that in step (3), PDPP is used as a modifier of the ethyl acetate anti-solvent at a concentration of 2.0 mg / ml.

[0058] Comparative Example 1

[0059] The difference from Example 1 is that in step (3), PDPP is not used as a modifier for the ethyl acetate anti-solvent.

[0060] Figure 1 The JV curves of the devices of Examples 1-3 and Comparative Example 1 are shown in Table 1. The specific parameters are listed in Table 1. It can be seen that the photoelectric performance of the perovskite solar cells of Examples 1-3 is significantly better than that of Comparative Example 1, mainly because the introduction of an appropriate amount of PDPP can significantly improve the power conversion efficiency (PCE) of the cell. The cell performance of Example 1 is the best. Compared with Comparative Example 1, its short-circuit current Jsc (24.30 mA / cm 2 ), open circuit voltage Voc (1.13V) and fill factor FF (77.79%) have been significantly improved.

[0061] Table 1 Main performance parameters of perovskite solar cells prepared in Examples 1-3 and Comparative Example 1

[0062]

[0063] Comparative Example 2

[0064] The difference from Example 1 is that in step (1), PDPP is replaced by ammonium polyphosphate.

[0065] Comparative Example 3

[0066] The difference from Example 1 is that in step (1), PDPP is replaced by polyethylene glycol.

[0067] Comparative Example 4

[0068] The difference from Example 1 is that in step (1), PDPP is replaced by polyparaphenylene.

[0069] Table 2

[0070]

[0071] Figure 2 is MAPbI of Examples 1-3 and Comparative Example 1 3 UV-Vis spectrum of perovskite film. The light absorption spectrum of the perovskite layer modified with 1.5 mg / ml PDPP (Example 1) was significantly improved compared with that of Comparative Example 1, showing its better light absorption capacity. The reason for this enhancement is mainly due to its dense surface morphology, increased grain size and separate complete cross-sectional morphology. On the other hand, a small amount of 1.0 mg / ml concentration (Example 2) or a slightly excessive amount of 2.0 mg / ml concentration (Example 3) of PDPP additive will result in a limited degree of enhancement in its light absorption capacity. The reason for this phenomenon may be that the inappropriate additive dosage leads to the increase of MAI and PbI 2 The unbalanced non-stoichiometric conditions in the solution state. Therefore, the crystallization of the perovskite grains and the film quality are unsatisfactory. The short-circuit current (Jsc) of the final device can be greatly improved from the higher sunlight utilization efficiency generated by the stronger light absorption ability of the perovskite film.

[0072] The embodiment 1 with the best device performance was compared with the comparative example 1 alone.

[0073] Figure 3 is the MAPbI of Example 1 and Comparative Example 1 3 Surface and cross-sectional SEM images of perovskite films, with a substrate structure of Glass / ITO / SnO 2 By applying the optimal 1.5 mg / ml PDPP doped antisolvent (Example 1), a fairly dense and smooth perovskite film with larger grain size and fewer grain boundaries was obtained. In contrast, the original MAPbI prepared in air environment, i.e., under the combined negative influence of higher humidity and other environmental factors, 3 The film (Comparative Example 1) has many small grains with more boundaries on its surface. This unsatisfactory morphology seriously affects the performance of the final device. Figure 3The cross-sectional SEM images of c and d show that the cross-sectional grains of the original perovskite film (Comparative Example 1) have more wrinkles, and multiple shrunken grains show an extrusion / laminated state in the cross-sectional direction, accompanied by some small grains and cracks. The perovskite film modified with 1.5 mg / ml PDPP (Example 1) is smoother, fuller, denser and more compact, with a single grain structure of the entire layer in the cross-sectional direction. Of course, except for whether PDPP is added to the anti-solvent ethyl acetate, other manufacturing parameters of different types of perovskite layers, such as spin coating speed, heating time, etc., are exactly the same.

[0074] MAPbI 3 The perovskite film was directly prepared on a glass substrate (without any conductive oxide) by spin coating and then subjected to PL testing, e.g. Figure 4 As shown in the figure, the PL spectrum test results clearly show that the PL intensity of the perovskite film modified with the optimal concentration of PDPP (Example 1) is significantly enhanced compared with the original perovskite layer (Comparative Example 1). This obvious improvement provides strong evidence for its suppressed non-radiative recombination.

[0075] Deposition on PEN / ITO / SnO 2 Optical and SEM images of the perovskite layer on a flexible substrate Figure 5 In the bending radius of 6mm, after 1000 bending cycles, the perovskite film of Example 1 can still present a tight and complete morphology. In sharp contrast, the original perovskite film of Comparative Example 1 shows many obvious cracks on its surface. These cracks may cause the electron transport layer at the bottom to directly contact the hole transport layer at the top, thus causing a short circuit, resulting in serious deterioration of device performance, and even irreparable damage. This result highlights the excellent bending resistance of the perovskite film modified with the optimal concentration of PDPP (Example 1).

[0076] like Figure 6 As shown, after the device of Example 1 (unpackaged) has undergone 1000 bending cycles at room temperature, its normalized PCE still maintains 78% of the initial value, which is much higher than that of Comparative Example 1 (23%). The reason for these significant improvements is mainly that the long flexible polymer chains of PDPP can gather at the perovskite grain boundaries and produce a double passivation effect through their strong chemical bonds, which enhances the crystallization of perovskite grains, improves the overall quality of the film (including defect-free surface and dense cross-sectional morphology), and ultimately protects the perovskite layer under the mechanical impact of repeated bending.

[0077] Figure 7The JV curves of the devices of Comparative Examples 2-4 are shown in Table 2. It can be clearly seen that the power conversion efficiency of the final solar cells prepared by modified perovskites of ammonium polyphosphate (PCE=20.87%), polyethylene glycol (PCE=20.12%) and polyparaphenylene (PCE=19.95%) is lower than that of Example 1. It should be emphasized that the data of various aspects (short-circuit current Jsc, open-circuit voltage Voc and fill factor FF) are significantly reduced compared with those of Example 1.

[0078] Figure 8 A schematic diagram of the chemical bonding process between the PDPP polymer chain and the perovskite lattice is shown. The extended polymer chain of PDPP is composed of alternating nitrogen and phosphorus elements, with abundant oxygen and benzene rings added on both sides. The phosphorus oxygen groups are able to form strong chemical bonds with lead (Pb) through Lewis acid-base interactions, while nitrogen can form hydrogen bonds with methylamine (MA). This double bond mechanism is used to simultaneously occupy the vacancies generated by I and Pb. The benzene rings show electroactive and hydrophobic properties, which are beneficial for improving the power conversion efficiency and stability of the device. At the same time, the flexible polymer chains have the ability to aggregate between the perovskite grain boundaries, thereby improving its ability to resist bending.

[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a bending-resistant perovskite film, characterized in that: The anti-bending perovskite film is obtained by spin-coating a MAPbI3 perovskite precursor solution on an electron transport layer and adding a modified anti-solvent, followed by thermal annealing. The MAPbI3 perovskite precursor solution includes a solute and a solvent, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the solute is lead iodide and methylamino iodide; the modified anti-solvent is ethyl acetate containing PDPP.

2. The preparation method according to claim 1, characterized in that: The concentration of the PDPP is 0.01-5.0 mg / ml.

3. The preparation method according to claim 1, characterized in that: The volume ratio of N,N-dimethylformamide to dimethyl sulfoxide in the solvent is 6-9:1, and the molar ratio of lead iodide to methylamino iodide in the solute is 1:

1.

4. The preparation method according to claim 1, characterized in that: The preparation method of the MAPbI3 perovskite precursor solution comprises: mixing a solute with a solvent, heating the mixture at 55° C. to 65° C., and stirring the mixture at a rotation speed of 200 to 500 rpm for 0.5 to 2 hours.

5. The preparation method according to claim 1, characterized in that: The spin coating lasts for a total of 40 seconds, and the process setting is divided into two sections; the first section is 10 seconds, and the rotation speed increases from static to 2000 rpm and maintains at an acceleration of 500 rpm / s; the second section is to continue spinning for 30 seconds without pausing, and the rotation speed increases from 2000 rpm to 3500 rpm at an acceleration of 1000 rpm / s.

6. The preparation method according to claim 1, characterized in that: The annealing temperature is 90° C. to 110° C., and the annealing time is 10 to 40 minutes.

7. The preparation method according to claim 1, characterized in that: The volume ratio of the modified anti-solvent to the MAPbI3 perovskite precursor solution is 100-500:

70.

8. The bending-resistant perovskite film obtained by the preparation method according to claims 1 to 7.

9. The bending-resistant perovskite film according to claim 8, characterized in that: The thickness of the bending-resistant perovskite film is 300-500 nm.

10. Use of the bending-resistant perovskite film in a perovskite solar cell according to claim 9, characterized in that: The preparation method of the perovskite solar cell comprises the following steps: preparing an anode, an electron transport layer, a photoactive layer, a hole transport layer and a cathode in sequence; wherein the photoactive layer is between the anode and the cathode, the electron transport layer is between the anode and the photoactive layer; the hole transport layer is between the cathode and the photoactive layer; the anode is ITO, the electron transport layer is SnO2, the photoactive layer is MAPbI3, the hole transport layer is Spiro-OMeTAD, and the cathode is Ag.